The Effect of E-Commerce on Community Entrepreneurial Interests in Curio District, Enrekang Regency - Erdi; Muh. Rizal S; Andi Muhammad Rivai; Risma Niswaty; Yusi Irensi Seppa (Business Research and Administration Innovation, 2025)
The Influence of E-commerce on Community Entrepreneurship Interest in Curio District, Enrekang Regency. Thesis. Business Administration Study Program. Faculty of Social Sciences and Law. Makassar State University. Guided by Muh. Rizal S and Andi Muhammad Rivai.This study aims to determine how the influence of e-commerce on entrepreneurial interest in the community in Curio District, Enrekang Regency. To achieve this goal, researchers use indicators to measure these variables. In the variables of e-commerce indikataor used, namely marketing, reputation, cost efficiency, expenses and ease of doing business online. As for the variables of entrepreneurial interest, the indicators used are feelings of pleasure, interest, attention and involvement. In this study, the research method used is a type of quantitative research, with data collection techniques carried out through observation, questionnaires and documentation. The sample used in this study was 100 respondents. Data was obtained from research results that were processed using data analysis and using the help of SPSS software program version 25 consisting of validity tests, reality tests, normality tests, simple linear regrrtion analysis, and coefficients of determination. The results showed that the indicators used on each of these variables showed that e-commerce variables had a significant influence on people's entrepreneurial interest in Curio District, Enrekang Regency. This is evidenced by a coefficient determination test using the data that has been obtained.